ضوابط حرية التعبير عن الرأي في الشريعة الإسلامية و المذاهب الفكرية المعاصرة - الورتي، ياسين عبدالله رسول; النعيمي، صلاح الدين محمد قاسم (بغداد, 2011)
This thesis is entitled “Regulations for Freedom of Speech in Islamic Shariaa and modern ideological approaches”. This is an important subject worthy to be explored mainly due to the important place this subject owns in the Islamic Shariaa, as well as due to the importance of language as the means of expressing one’s ideas. Meanwhile, nowadays freedom of speech has turned into an important subject for heated discussion and debates between the fervent supporters of complete freedom of speech and those who support the restriction of this freedom. Islam is supporting disciplined and regulated freedom. So far the Islamic regulations and laws regarding the freedom of speech are not collected in an academic thesis. Since there is a necessity for making these regulations and laws accessible for Islamic scholars and all Muslims in general I decided to choose this subject for my research. Exploring this subject demands the definition of the terms ‘freedom’, ‘regulations’, ‘expressing’ and ‘opinion’ in the introductory chapter. The first chapter is allocated to discussing the viewpoint of Islam as well as modern doctrines regarding freedom. The second chapter includes the discussion on the freedom of speech and its place among public or general freedoms and the view of Islamic Shariaa regarding this issue. Later, the third chapter includes the Islamic regulations regarding the freedom of speech. Finally, the thesis arrives at a number of conclusions; some of the important ones are as follows: 1. In Islamic Shariaa, freedom is a gift from Allah and a portion of Allah’s reverence for human beings. It is a legitimate right that cannot be denied from human beings. However, this freedom is not an absolute freedom, but a freedom restricted and regulated according to Islamic regulators. 2. Freedom of speech is one of the important types of freedom which reflects the real character of human beings and a number of other freedoms are regarded as its branches, such as religious freedom (freedom of performing religious customs and prayers), freedom of press, freedom of association and assembly, political freedoms and freedom of practicing art. 3. Freedom of Speech has a special place in Islam. This is due to Islam’s respect for human reason as a source for establishing opinion and views as well as the responsibility of human beings for expressing the truth. That’s why Islam has left a big legislation gap in worldly affairs for the human opinion. 4. Individual Muslims as well as Islamic associations must follow the Islamic regulators in expressing their views, especially in the mass media. 5. Legitimate regulations (regarding the freedom of speech) cover different aspects of the freedom of speech including: a. The personality of the person who expresses his opinion b. The content of the opinion and the field the opinion is made about c. The aims behind expressing this opinion and the results of this opinion d. The means and methods used for expression the opinion In the conclusion I pray from Allah to accept this work with all its defects from me and I testify that all the achievements and good things in this research are the result of Allah’s mercy and kindness for me and all the defects in the thesis are from me.
Keywords: حرية التعبير -- حرية الرأي -- الشريعة الإسلامية -- الحريات العامة